2012
DOI: 10.1016/j.molbiopara.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of the ceramide synthase from Trypanosoma cruzi

Abstract: In this study, we characterized ceramide synthase (CerS) of the protozoan parasite Trypanosoma cruzi at the molecular and functional levels. TcCerS activity was detected initially in a cell-free system using the microsomal fraction of epimastigote forms of T. cruzi, [3H]dihydrosphingosine or [3H]sphingosine, and fatty acids or acyl-CoA derivatives as acceptor or donor substrates, respectively. TcCerS utilizes both sphingoid long-chain bases, and its activity is exclusively dependent on acyl-CoAs, with palmitoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 81 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…CerS activity has been identified [54] and characterized at the biochemical and molecular levels only in T. cruzi ([63], submitted). The TcCerS was initially identified by the incorporation of [ 3 H]palmitic acid into ceramides, which were chemically degraded to radiolabeled dihydrosphingosine and fatty acid [54].…”
Section: Ceramide Synthase: the Central Axis Of The Sbpsmentioning
confidence: 99%
“…CerS activity has been identified [54] and characterized at the biochemical and molecular levels only in T. cruzi ([63], submitted). The TcCerS was initially identified by the incorporation of [ 3 H]palmitic acid into ceramides, which were chemically degraded to radiolabeled dihydrosphingosine and fatty acid [54].…”
Section: Ceramide Synthase: the Central Axis Of The Sbpsmentioning
confidence: 99%
“…However, enzyme activities for Leishmania are not yet characterized, and so far are based on or inferred from the final SL biosynthetic product: IPC ceramide structure. In regard to other trypanosomatids, Figueiredo et al ( 2012 ) reported that TcCerS in T. cruzi preferentially uses dihydrosphingosine base as sphingosine base and palmitoylCoA as substrate, and Sevova et al ( 2010 ) showed that specific SL synthases in T. brucei, T. cruzi , and L. major transfer polar head groups from phosphoglycerolipid donors to generate SM, ethanolamine phosphorylceramide, and IPC using 6-(( N -(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)hexanoyl)sphingosine C 6 -ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…However, clear divergence is observed in the second and the third steps, both of which represent a cell-fate modulator process. CerSs exhibit differential preferences for the chain length of the acyl-CoA substrate (Park et al 2014 ) and its hydroxylation pattern (Layre & Moody, 2013 ), with 6 isoforms present in humans suggesting a different role for each CER species produced (Levy & Futerman, 2010 ; Figueiredo et al 2012 ). To-date, one or, maximum, two genes encoding CerS function have been identified in protozoan parasite species (Koeller & Heise, 2011 ).…”
Section: Sl Metabolismmentioning
confidence: 99%
“…Experimental evidence (from our laboratory and others) has previously indicated the presence of CerS activity in Leishmania spp (Zhang et al , 2003 ; Denny et al , 2004 , 2006 ) and in T. cruzi (De Lederkremer et al 2011 ). More recently LAG1 orthologues have been identified and functionally and molecularly characterized in the latter parasite (Figueiredo et al 2012 ). Other results indirectly suggest the presence of such activity in T. brucei (Patnaik et al 1993 ; Richmond et al 2010 ; Smith & Bütikofer, 2010 ).…”
Section: Sl Metabolismmentioning
confidence: 99%
See 1 more Smart Citation